Nuclear Medicine Therapy With 223Radium-dichloride for Osseous Metastases in Prostate Carcinoma. (January 2019) - Wale, Daniel J.; Viglianti, Benjamin L.; Gross, Milton D.; Ferretti, Alice; Rubello, Domenico; Wong, Ka Kit
Abstract : Painful osseous metastasis resulting from castration-resistant prostate carcinoma is a common clinical problem. Historically, nuclear medicine offered several palliative beta-emitting radiopharmaceuticals targeting the skeleton with the goal of decreasing pain. However, these have largely been replaced by the alpha-emitting agent 223 radium (Ra). 223 Ra received Food and Drug Administration approval in 2013 for the treatment of metastatic castration-resistant prostate cancer with symptomatic bone metastases without visceral metastases. 223 Ra offers an improved therapeutic profile due to its alpha-particle emissions resulting in a relatively higher linear energy transfer and lower particle range compared with beta-emitters. 223 Ra also has demonstrated to increase overall survival in patients and to delay adverse skeletal events. Running a successful clinical nuclear therapy program with 223 Ra requires a multidisciplinary team approach and this article suggests an implementation strategy from the authors' institution. Potential new nuclear radiopharmaceuticals still under investigation offering the future possibility of radioligand therapy are also discussed briefly.